Antimicrobial and cytotoxic synergism of biocides and quorum-sensing inhibitors against uropathogenic Escherichiacoli. (April 2023) - Capper-Parkin, K.L.; Nichol, T.; Smith, T.J.; Lacey, M.M.; Forbes, S.
Summary: Background: Uropathogenic Escherichia coli (UPEC) are a primary cause of catheter-associated urinary tract infections (CAUTIs), often forming mature recalcitrant biofilms on the catheter surface. Anti-infective catheter coatings containing single biocides have been developed but display limited antimicrobial activity due to the selection of biocide-resistant bacterial populations. Furthermore, biocides often display cytotoxicity at concentrations required to eradicate biofilms, limiting their antiseptic potential. Quorum-sensing inhibitors (QSIs) provide a novel anti-infective approach to disrupt biofilm formation on the catheter surface and help prevent CAUTIs. Aim: To evaluate the combinatorial impact of biocides and QSIs at bacteriostatic, bactericidal and biofilm eradication concentrations in parallel to assessing cytotoxicity in a bladder smooth muscle (BSM) cell line. Methods: Checkerboard assays were performed to determine fractional inhibitory, bactericidal, and biofilm eradication concentrations of test combinations in UPEC and combined cytotoxic effects in BSM cells. Findings: Synergistic antimicrobial activity was observed between polyhexamethylene biguanide, benzalkonium chloride or silver nitrate in combination with either cinnamaldehyde or furanone-C30 against UPEC biofilms. However, furanone-C30 was cytotoxic at concentrations below those required even for bacteriostatic activity. A dose-dependent cytotoxicity profile was observed for cinnamaldehyde when in combination with BAC, PHMB or silver nitrate. Both PHMB and silver nitrate displayed combined bacteriostatic and bactericidal activity below the half-maximum inhibitory concentration (IC50 ). Triclosan in combination with both QSIs displayed antagonistic activity in both UPEC and BSM cells. Conclusion: PHMB and silver in combination with cinnamaldehyde display synergistic antimicrobial activity in UPEC at non-cytotoxic concentrations, suggesting potential as anti-infective catheter-coating agents.